Effects of combining running and practical duration stretching on proprioceptive skills of national sprinters - Romero-Franco, N.; Párraga-Montilla, J. A.; Molina-Flores, E. M.; Jiménez-Reyes, P. (The Journal of Strength and Conditioning Research, 2020)
Practical duration stretching after aerobic activities is a recommended component of the first part of warm-up because of its effects on performance. However, its effects on proprioceptive skills are unknown. This study aimed to analyze the effects of running and practical duration static stretching (SS) and dynamic stretching (DS) on postural balance and the joint position sense (JPS) of national sprinters. Thirty-two national sprinters were randomly classified into a SS group (n = 11), DS group (n = 11), or control group (n = 10). Static stretching performed 5 minutes of running and short-duration (20 seconds) static stretches; DS performed 5 minutes of running and short-duration dynamic (20 seconds) stretches; and the control group performed 5 minutes of running. Before and after the intervention, unipedal static postural balance and knee JPS were evaluated. Static stretching exhibited a more centralized center of pressure in the medial-lateral plane for unipedal static postural balance in right-leg support after stretching (p = 0.005, d = 1.24), whereas DS showed values further from the center after stretching for the same unipedal support compared with baseline (p = 0.042, d = 0.49), and the control group remained stable (p > 0.05). Joint position sense did not show significant differences in any group (p > 0.05). In conclusion, combining running and practical duration SS may be beneficial for right-leg postural stabilization, whereas DS may be partly and slightly deleterious. Both SS and DS combined with running and running alone have neutral effects on knee JPS. Sports professionals should consider running and practical duration SS as part of the warm-up of sprinters to partly improve unipedal static postural balance.